2009
DOI: 10.1002/eji.200838509
|View full text |Cite
|
Sign up to set email alerts
|

Human natural Treg microRNA signature: Role of microRNA‐31 and microRNA‐21 in FOXP3 expression

Abstract: Treg are the main mediators of dominant tolerance. Their mechanisms of action and applications are subjects of considerable debate currently. However, a human microRNA (miR) Treg signature has not been described yet. We investigated human natural Treg and identified a signature composed of five miR (21, 31, 125a, 181c and 374). Among those, two were considerably under-expressed (miR-31 and miR-125a). We identified a functional target sequence for miR-31 in the 3 0 untranslated region (3 0 UTR) of FOXP3 mRNA. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(254 citation statements)
references
References 30 publications
13
233
2
2
Order By: Relevance
“…miR-21 was found to be highly represented in effector and memory T cells compared with naive CD8 + T cells (50). In human Tregs, miR-21 was found to act as a positive, although indirect, regulator of FOXP3 expression (51). Furthermore, miR-21 was found to be overexpressed in CD4 + T cells derived both from patients with lupus and from lupus-prone MRL/lpr mice (52).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 was found to be highly represented in effector and memory T cells compared with naive CD8 + T cells (50). In human Tregs, miR-21 was found to act as a positive, although indirect, regulator of FOXP3 expression (51). Furthermore, miR-21 was found to be overexpressed in CD4 + T cells derived both from patients with lupus and from lupus-prone MRL/lpr mice (52).…”
Section: Discussionmentioning
confidence: 99%
“…The modifiable mediators of this regulation include methylation,37, 38, 39, 40, 41, 42, 43, 44 acetylation45, 46, 47 and microRNA‐mediated control of transcript translation 28, 48, 49, 50, 51, 52, 53, 54, 55. The global regulation of FOXP3 is influenced by chromatin organises, including SATB1 acts both during development and in mature cells 48, 58.…”
Section: Foxp3 Epigenetic Regulationmentioning
confidence: 99%
“…57 In addition, miR-21 and miR-31 regulate Treg development by changing Foxp3 expression. 58 Several miRNAs have been reported to promote Th17 cell development. For example, miR-326 facilitates Th17 development and accelerates the progression of autoimmunity by directly inhibiting ETS1, which is a negative modulator of Th17 differentiation.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%
“…68 miR-31 has been demonstrated to reduce Foxp3 expression. 58 Similar to miR-101, miR-26a has also been shown to target Ezh2, which is related to Foxp3 expression and the suppressive functions of nTregs. 68 Jeker et al found that miR-10a expression was lower in Tregs from NOD mice than in Tregs from autoimmunity-resistant C57BL/ 6 mice.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%